Efficacy and safety of ripertamab for treating primary membranous nephropathy among adults: a multicenter, retrospective, real-world study - Wang, Xichao; Song, Xinyuan; Sun, Na; Chang, Wenxiu (Frontiers in Immunology, 2025)
BackgroundRipertamab has been used in an off-label manner for treating primary membranous nephropathy (PMN) in real-world settings in China, despite limited evidence supporting the efficacy of this drug. This multicenter, retrospective study is the first to assess the effectiveness and safety of ripertamab for treating PMN in a real-world Chinese clinical setting.MethodsAdult patients with PMN who were treated with at least one course of ripertamab alone were included in this study. Patients were categorized into two groups based on their prior treatment of PMN: the initial therapy group and the non-initial therapy group. The primary outcome was the occurrence of complete remission (CR) or partial remission (PR) at 6 and 12 months. The secondary outcomes included the time to achieve remission, relapse rate and the incidence of adverse events (AEs).ResultsFifty-two patients were ultimately included for analysis. Among these patients, 39 received ripertamab as initial therapy, while 13 were in the non-initial therapy group. The median follow-up duration was 8.7 (4.7, 11.3) months. At 6 months, 24/40 (60.0%) patients achieved clinical remission, with 2/40 (5.0%) achieving CR and 22/40 (55.0%) achieving PR. At 12 months, 22 patients completed follow-up: 2 (9.1%) achieved CR, and 15 (68.2%) achieved PR. The median time to remission for the entire cohort was 90.5 (32, 165) days and four of the 52 patients (7.7%) relapsed. The initial therapy group had a higher remission rate at 12 months than the non-initial therapy group [13/15 (86.7%) vs. 4/7 (57.1%)]. Additionally, the initial therapy group achieved remission more quickly than the non-initial therapy group [79.0 (36, 112) vs. 165.0 (30, 313) days]. Ripertamab was well tolerated, with 9.6% (5/52) of patients experiencing AEs; none of the AEs were severe.ConclusionRipertamab demonstrated efficacy and good tolerability for the treatment of PMN in a Chinese real-world setting. These findings support the use of ripertamab as a therapeutic option for PMN patients and suggest the need for further investigation into its long-term safety and efficacy.